Upaya Meningkatkan Motivasi Belajar IPS Melalui Strategi Index Card Match pada Siswa Kelas IX SMP Negeri 5 Taliwang - M. Zainuddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
The objectives to be achieved in this Classroom Action Research are to determine the effectiveness of the Index Card Match learning strategy in increasing student motivation towards social studies subjects. This Classroom Action Research was conducted at Taliwang 5 Public Middle School on 21st-grade students. Data collection is done by observation, interview questionnaire, documentation, and field notes. Data analysis in this study was carried out by qualitative analysis. The results of the analysis showed an increase in student motivation by using the Index Card Match strategy can be seen in the first cycle only 60%, while in the second cycle to 89%. The planning of learning by the teacher increased by 75% in the first cycle, the second cycle became 95% as well as the implementation of learning increased from 70% in the first cycle to 90% in the second cycle. The attitude of students towards learning by using the Index Card Match strategy received a positive response. This can be seen in the two cycles of the statement of attitude in the first cycle 50% and 92% cycle